Analysis of Mechanical Response for a Reinforced Bedded Rock Slope under Rainfall - Longqi Li; Changlin Li; Chuan He (Advances in Civil Engineering)
This paper has the objective to reveal real-time responses at several locations in reinforced bedded rock slopes under different rainfall conditions. Four scaled model tests have been conducted by varying rainfall patterns and slope inclinations, while several sensors, including fiber Bragg grating (FBG) displacement sensors, pore pressure sensors, and miniature pressure gauges, were instrumented in layers to capture corresponding responses during and after rainfall. The results show that the the slide of a reinforced bedded rock slope has a locking section, and the ultimate displacement under long-term medium rainfall was about three times larger than that under short-term storm rainfall. Meanwhile, the short-term storm rainfall generated little influence on the deeper pore pressure for reinforced bedded rock slope. The pore pressure at the surface layer was initially larger and then smaller than that at the intermediate layer for the same slope. For the slope under long-term medium rainfall, the shift moment was at 11.5 hours after testing started, while for the slope under short-term storm rainfall, the shift moment was at 3.5 hours after testing started. The thrust pressure ascended with the rainfall persisting and descended a little after rainfall. The descending in thrust pressure was mainly due to the fact that the strength of slope mass recovered partially with water flowing out of the slope from the frontal portion and the slide tendency was weakened. These results can provide engineers with more acquaintance with response characteristics for these kinds of rock slope.